Shanghai ghetto [videorecording (DVD)] - Mann, Amir; Janklowicz-Mann, Dana; Landau, Martin, 1928-2017 (New Video Group, 2004)
The incredible story of thousands of Jews and their dramatic escape from the Nazis to China during World War II.